Integrating Heutagogy and Flipped Learning in Islamic Higher Education: A Framework for Knowledge Construction and Self-Directed Learning - Fathiyatul Haq Mai Al Mawangir; Sutrisno Sutrisno; Muhammad Nasir (STAI Hubbulwathan Duri, 2025)
The digital revolution has reshaped many sectors, including education. However, Islamic higher education institutions often remain bound by traditional methods, limiting their ability to support 21st-century learning, which values flexibility, accessibility, and learner autonomy. This study employs a literature review with a contextual and thematic analysis approach. It uses content analysis to explore the integration of the heutagogical approach and the flipped learning model within Islamic higher education settings. Findings reveal that heutagogical learning design should rest on four key principles: flexibility, learner agility, negotiated learning, and inquiry-based instruction. These principles are operationalized through six core components—explore, create, collaborate, connect, reflect, and share. Implemented through flipped learning, these elements encourage self-directed learning both before and after classroom sessions, enhancing learner engagement and addressing limitations in conventional instructional models. The synergy between heutagogy and flipped learning provides a viable framework for Islamic higher education to foster knowledge construction and autonomy. This approach not only modernizes pedagogical practices but also aligns with the Islamic objective of developing insan kamil—holistic individuals grounded in monotheism and moral character, equipped for lifelong, independent learning.